PELATIHAN DIGITAL MARKETING UNTUK MENINGKATKAN DAYA SAING UMKM OLEH-OLEH KHAS KECAMATAN PAMIJAHAN KABUPATEN BOGOR : PELATIHAN DIGITAL MARKETING UNTUK MENINGKATKAN DAYA SAING UMKM OLEH-OLEH KHAS KECAMATAN PAMIJAHAN KABUPATEN BOGOR - Dewi Purwati; Susi Melinasari; Keris Kartono (Lembaga Penelitan dan Pengabdian Masyarakat Institut Agama Islam Sahid, 2026)
Pamijahan District, Bogor Regency, has significant tourism potential, but Micro, Small, and Medium Enterprises (MSMEs) producing local souvenirs still rely on traditional marketing. This lack of a digital footprint hinders the competitiveness of local products in an increasingly modern market. This community service initiative aims to bridge this digital divide through digital marketing training, focusing on visual design using the Canva platform. The Participatory Action Research (PAR) method involved active community participation, from problem identification and discussion to hands-on action implementation, to evaluation. The mentoring program demonstrated improved skills among MSMEs in compiling digital product catalogs, designing business logos, applying color psychology, and creating aesthetic promotional content for social media. The use of Canva features has proven effective in enhancing the perceived value and professionalism of MSME products. In conclusion, this training has successfully increased the independence and digital competitiveness of Pamijahan MSMEs, opened up opportunities for market share expansion, and contributed to improving the economic well-being of the community in the tourism area.